The revival of agricultural lease - Czechowski, Paweł; Niewiadomski, Adam (Przegląd Prawa Rolnego, 2024)
The article discusses the challenges facing agricultural lease in European and national regulations. It presents the rich achievements of the initiator of the research on lease, Professor Aleksander Lichorowicz. The authors emphasised the traditional role of lease and its peculiar civil law character, and highlighted the dualism of the regulation of the lease of private agricultural real estate and the agricultural real estate of the State Treasury. An assessment of the new function and challenges of lease in the context of the challenges of agricultural real estate turnover and the leaseholder’s statutory right of first refusal has also been made and then followed by a discussion of the issues related to the social security of farmers, direct subsidies to the leased land, or other aid measures from public tributes. In conclusion, as de lege ferenda conclusions, the authors formulated proposals for legislative changes concerning agricultural lease.